A review on the mechanics of carbon nanotube strengthened deformable structures. (1st October 2020) - Khaniki, Hossein Bakhshi; Ghayesh, Mergen H.
Abstract: Carbon nanotubes (CNTs) have become an important element in strengthening elastic structures. Different types of CNT strengthened structures have been fabricated in the past decades each with different applications and advantages. This review paper highlights the efforts performed on producing CNT strengthened deformable structures, fabrication procedure, and modelling and analysing the mechanical behaviour by focusing mainly on engineered CNT distributions through the matrix. Since combining high amounts of CNTs with matrix could be costly, the papers concentrating on the importance of grading, aligning and positioning the CNT fibres in order to reach the highest efficiency are also reviewed. Moreover, the influence of different types of CNT grading on static, stability and dynamic response of different types of structures in the frameworks of both linear and non-linear analyses is discussed.